Ontogenetic constraints on foraminiferal test construction. Issue 3 (May 2017) - Caromel, Aude G. M.; Schmidt, Daniela N.; Rayfield, Emily J.
Abstract : Developmental processes represent one of the main constraints on the generation of adult form. Determining how constructional and energetic demands operate throughout growth is essential to understanding fundamental growth rules and trade‐offs that define the framework within which new species originate. In organisms producing spiral shells, coiling patterns can inform on the constructional constraints acting throughout development that dictated the diversification of forms within a group. Here, we use Synchrotron radiation X‐Ray tomographic microscopy (SRXTM) reconstructions of eight planktic foraminifera representative of the major morphotypic groups to determine disparity of coiling patterns by measuring Raupian parameters. The results show that foraminifera are a morphologically highly conservative group, exploiting a limited range of potential coiling patterns. Very similar coiling patterns during early ontogeny, regardless of species, point toward strong constraints in early ontogeny and to common developmental processes acting across all morphogroups. Dispersion and lateral displacement of taxa in morphospace are limited to the adult stage. Accretion with low translation down the coiling axis in juveniles may maximize lateral growth and metabolic efficiency in light of costly calcification. Increased translation in the adult stages allows growth to accommodate new chamber shapes, mediated by changes in aperture location and the site of accretion over ontogeny. These constructional constraints, and the accretion of a small number of discrete chambers, limit the potential for novel forms within the foraminifera compared to other groups of coiling organisms and may explain the repeated evolution of similar morphotypes throughout the evolutionary history of the group.